EFFECT OF BENZENE ON BLOOD PARAMETERS OF MALE MICE - Al-Maliki, Sami (University of Thi-Qar Journal of Science, 2019)
Super and ordinary benzene were used to examine the effect of benzene on blood parameters of male mice .Three stages with five treated groups were used. The first stage was after the end of injection period. The second stage was after 45 days from the end of injection period. Third stage was after 90 days from the end of injection period. I.P. injection was used. The results of this study indicate the decline of all blood parameters with more reduction in the mice that were experimented directly after the third injection ( first stage) .Such reduction seems to be slight in animals experimented on 45 days after the last injection (second stage ) and little or absent in these were experimented 90 days after the last injection (third stage ) .